Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.7726/ajad.2013.1006
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness and Semantic Fluency in Alzheimer’s Disease and Mild Cognitive Impairment

Abstract: The hallmark of Alzheimer's disease (AD) is declarative memory loss, but deficits in semantic fluency are also observed. We assessed how semantic fluency relates to cortical atrophy to identify specific regions that play a role in the loss of access to semantic information. Whole-brain structural magnetic resonance imaging (MRI) data were analyzed from 9 Normal Control (NC)(M=76.7, SD=5.6), 40 Mild Cognitive Impairment (MCI) (M=74.4, SD=8.6), and 10 probable AD (M=72.4, SD=8.0) subjects from the Alzheimer's Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…Specifically, some MRI studies have reported a cortical atrophy in the (left) prefrontal cortices in individuals with amnestic or non-amnestic MCI (Pa et al, 2009 ; Wang et al, 2009 ; Chang et al, 2010 ; Ahn et al, 2011 ; Zhao et al, 2015 ). In addition, a link between poor semantic fluency performance and cortical atrophy of the lateral prefrontal regions (especially in the left hemisphere) has also been reported in these individuals (Ahn et al, 2011 ; Eastman et al, 2013 ; Clark et al, 2014 ). Furthermore, some fMRI studies have shown that these individuals exhibit abnormal frontal activations while performing various cognitive tasks, including episodic memory retrieval (Heun et al, 2007 ), semantic memory (Woodard et al, 2009 ), divided attention (Dannhauser et al, 2005 ), interference control (Kaufmann et al, 2008 ; Van Dam et al, 2013 ), and working memory (Alichniewicz et al, 2012 ; Papma et al, 2013 ; see Li et al, 2015 , for a recent meta-analysis of fMRI studies in MCI).…”
Section: Introductionmentioning
confidence: 83%
“…Specifically, some MRI studies have reported a cortical atrophy in the (left) prefrontal cortices in individuals with amnestic or non-amnestic MCI (Pa et al, 2009 ; Wang et al, 2009 ; Chang et al, 2010 ; Ahn et al, 2011 ; Zhao et al, 2015 ). In addition, a link between poor semantic fluency performance and cortical atrophy of the lateral prefrontal regions (especially in the left hemisphere) has also been reported in these individuals (Ahn et al, 2011 ; Eastman et al, 2013 ; Clark et al, 2014 ). Furthermore, some fMRI studies have shown that these individuals exhibit abnormal frontal activations while performing various cognitive tasks, including episodic memory retrieval (Heun et al, 2007 ), semantic memory (Woodard et al, 2009 ), divided attention (Dannhauser et al, 2005 ), interference control (Kaufmann et al, 2008 ; Van Dam et al, 2013 ), and working memory (Alichniewicz et al, 2012 ; Papma et al, 2013 ; see Li et al, 2015 , for a recent meta-analysis of fMRI studies in MCI).…”
Section: Introductionmentioning
confidence: 83%
“…Interestingly, the GMV observed to be decreased bilaterally for the pars orbitalis may be related to known deficits in semantic fluency [39], [40].…”
Section: G Connectivity Analysis Lmci Vs Admentioning
confidence: 95%
“…The Verbal Fluency Test (VFT) 14 , widely used in Brazilian studies for the early identification of cognitive decline 15 , seeks to verify language, semantic memory and executive functions, evaluating the ability to search and retrieve data established in long-term memory. The VFT, which is based on categories, shows great sensitivity 16 in distinguishing individuals without cognitive alterations from those in early stages of AD 17 .…”
Section: Introductionmentioning
confidence: 99%